(Not) everyone can be a winner: The role of payoff interdependence for redistribution - Sebastian Schaube; Louis Mick Strang (University of Bonn and University of Cologne, Reinhard Selten Institute (RSI), 2022)
Frequently, one person's success comes at the expense of others. We contrast such zero-sum environments in which individuals' payoffs are interdependent to those where payoffs are independent. In a laboratory experiment, we study whether the resulting inequality is perceived differently and how this affects redistribution. Across treatments, we compare a spectator's redistribution of two workers' earnings. If workers do not compete in a zero-sum setting, average redistribution decreases. In a representative survey, we replicate this finding and document that individuals who believe in a zero-sum world support higher levels of redistribution and are more likely to be Democrats.
Keywords: C91; D31; D63; H23; 330; Redistribution; Fairness; Zero-sum; Social preferences; Lab experiment